International Dental Aid and WWII - Riaud, Xavier (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
During the liberation of the camps, a great majority of the detainees died after eating abundantly within a shortperiod of time. A thousand men died because the Americans and the Englishmen were totally bewildered andoverwhelmed with what was in front of them. In good faith, they gave a great amount of food to the survivorswithout thinking of the dramatic consequences that this was going to cause. Indeed, the survivors’ weakenedbodies could not bear too much food. As a result, they changed their minds and they set up field hospitals whichwere to feed the sick through successive steps.